Kadar Makronutrien Dan Nilai Indeks Glikemik Tepung Umbi Suweg (Amorphophallus campanulatus) Dengan Dan Tanpa Difermentasi - Dian Ratih Laksmitawati; Umi Marwati; Vergie Indriani (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Low-glycemic indexed foods are increasingly in demand. The glycemic index value is influenced by macronutrient composition. Fermentation can change macronutrient levels of foods. This study aims to analize the effect of lactic acid bacteria fermentation on macronutrient content (protein, fat, carbohydrate) and glycemic index of suweg (Amorphophallus campanulatus) tuber flour. Tuber were thinly sliced, fermented with 10% lactic acid bacteria T1-2 isolated from previous studies, then incubated at room temperature for 4 days. The fermented tuber was then made into flour. The fermented suweg flour was tested to determine the glycemic index using experimental mice. Macronutrient levels of carbohydrates, fats and proteins are chemically determined. The results showed that during the lactate acid bacteria fermentation process 0-4 days there was an increase of lactat acid bacteria viability from day 0 to day 2 (3,64x108- 20,38x108 cells / ml) and decreased after day 2 (14,63x108- 7,91x108 cells / ml), the total acid count increased (0,2066% -1,2599%) as the pH decreased (5,43-4,37). The determination respectively result of protein, fat and carbohydrate contents of fermented suweg fluor was 7,41%, 0,46% and 0,38% and 6,05%, 0,38% , 82,15% in non fermented suweg fluor. The glycemic index value of fermented suweg flour was 64,6 and 69,4 in non fermented fluor. Based on statistical test, macronutrient content (fat, carbohydrate, protein) and glycemic index showed no significant difference between fermented and non fermented suweg fluor (P> 0,05). Fermentation of the lactic acid bacteria on suweg tuber for four days had no effect on the glycemic index and carbohydrate, fat and protein levels on the tubers.